Genetic assessment of Staphylococcus aureus in an underreported locality: Ambulatory care clinic. Issue 5 (September 2018) - Lawrance, Matthew F.; Muthukrishnan, Gowrishankar; Deichen, John; Deichen, Michael; Schaus, James; Cole, Alexander M.; Parkinson, Christopher L.
Abstract: Background: Staphylococcus aureus has strong association with anthropogenic environments. This association has not been well supported by use of genetic tools. The aim of this study was to phylogenetically relate numerous isolates from three environments — NCBI samples from hospitals, a community, and a previously unexplored healthcare environment: an ambulatory care clinic (ACC). Methods: This study incorporated hospital samples from NCBI, a community database from the University of Central Florida (UCF), and newly added samples taken from employees of an ambulatory care clinic located at UCF. Samples were collected from nasal swabs of employees, and positive samples were cultured, extracted, and sequenced at seven MLST loci and one virulence locus (spa). MLST sequences were used in eBURST and TCS population structure analyses and all sequences were incorporated into a phylogenetic reconstruction of relationships. Results: A total of 185 samples were incorporated in this study (15 NCBI sequences from hospital infections, 29 from the ACC, and 141 from the community). In both phylogenetic and population genetics analyses, samples proved to be panmixic, with samples not segregating monophyletically based on sample origin. Conclusion: Samples isolated from ambulatory care clinics are not significantly differentiated from either community or hospital samples at the representative loci chosen. These results strengthen previous conclusions that S. aureus may exhibit high genetic similarity across anthropogenic environments.